2019
DOI: 10.21203/rs.2.9640/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The bacteriostatic effect and mechanism of berberine on Methicillin resistant Staphylococcus aureus in vitro

Abstract: Background: To observe the bacteriostatic effect of berberine on MRSA, while also exploring the bacteriostatic mechanism of BBR on MRSA. Methods: The MIC of BBR, gentamicin, levofloxacin,amikacin was determined by broth microdilution, while the MICs of BBR combined with gentamicin, levofloxacin,amikacin against MRSA were determined using microdilution checkerboard. Time-killing test were used to determine the kinetics of BBR combined with antibiotics for MRSA. We used conductivity to assess the changes in mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Similarly, MRSA adhesion and intracellular invasion were notably decreased post treatment with berberine (Yu et al, 2005). Moreover, expression of MRSA cell wall hydrolysis, serine protease (Wang et al, 2020), and biofilm (Zhang et al, 2022)-associated genes were significantly repressed following treatment with berberine. A previous study demonstrated that higher doses of berberine were more effective in increasing cell membrane permeability of MRSA (Xia et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, MRSA adhesion and intracellular invasion were notably decreased post treatment with berberine (Yu et al, 2005). Moreover, expression of MRSA cell wall hydrolysis, serine protease (Wang et al, 2020), and biofilm (Zhang et al, 2022)-associated genes were significantly repressed following treatment with berberine. A previous study demonstrated that higher doses of berberine were more effective in increasing cell membrane permeability of MRSA (Xia et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The content of MDA can reflect the degree of lipid peroxidation in the body or organs. Yonar et [10] al. took rainbow trout as the research object and tested the antioxidant activity of ellagic acid at 50, 100 and 150 mg/kg mb respectively.…”
Section: Antioxidant Effectsmentioning
confidence: 99%